2011
DOI: 10.1029/2010ja016287
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of interplanetary magnetic field ∣By∣ on polar cap patch formation

Abstract: [1] A number of poleward moving events were observed between 1130 and 1300 UT on 11 February 2004, during periods of southward interplanetary magnetic field (IMF), while the steerable antenna of the European Incoherent Scatter (EISCAT) Svalbard radar (ESR) and the Tromsø VHF radar pointed nearly northward at low elevation. In this interval, simultaneous SuperDARN CUTLASS Finland radar measurements showed poleward moving radar aurora forms (PMRAFs) which appeared very similar to the density enhancements observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 79 publications
(131 reference statements)
9
94
0
Order By: Relevance
“…5d, where fast flows of >~1500 m/s are predominantly seen during large |By| and small |Bz|. Under a large IMF By condition, it has been observed that mesoscale flows in the cusp region propagate poleward, and this has been suggested to be due to large tension force in dayside reconnection under large IMF |By| (Sandholt et al 2004;Lockwood et al 2005;Rinne et al 2010;Zhang et al 2011Zhang et al , 2013b. Combining with our observation, these mesoscale flows may move far away from the noon meridian and then propagate into the polar cap.…”
Section: Imf By and Bz Dependencesupporting
confidence: 59%
See 2 more Smart Citations
“…5d, where fast flows of >~1500 m/s are predominantly seen during large |By| and small |Bz|. Under a large IMF By condition, it has been observed that mesoscale flows in the cusp region propagate poleward, and this has been suggested to be due to large tension force in dayside reconnection under large IMF |By| (Sandholt et al 2004;Lockwood et al 2005;Rinne et al 2010;Zhang et al 2011Zhang et al , 2013b. Combining with our observation, these mesoscale flows may move far away from the noon meridian and then propagate into the polar cap.…”
Section: Imf By and Bz Dependencesupporting
confidence: 59%
“…It is known that for large, negative By, the boundary between dawn and dusk convection cells is shifted toward dawn in the southern hemisphere (Reiff and Burch 1985;Lyons et al 1996) and toward dusk in the northern hemisphere (Weimer 2005). Additionally, the previous case studies have shown the IMF By-related formation of polar cap patches (Lockwood et al 2005;Zhang et al 2011Zhang et al , 2013b. In our study, we statistically showed that the departing points of these patches from the poleward boundary of auroral oval are associated with IMF By, and moreover, the airglow patches that depart at <9 MLT are with strong negative By.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7a). These suggest that the transient reconnection (FTE) leads to the erosion of the OCB equatorward to a region of higher density plasma (the solar EUV ionized plasma), followed by poleward relaxation of that boundary carrying with it the high density plasma accelerated into the polar flow (Lockwood and Carlson, 1992;Zhang et al, 2011). The plasma flow has a poleward component for most of the time between 09:00 UT and 12:00 UT (see the fourth panel of Fig.…”
Section: Eiscat Measurementsmentioning
confidence: 99%
“…(Zhang et al, 2017), but, if they appear only in 630.0 nm keogram ( Figure 1B), so called polar cap patches (e.g., Sato et al, 1998;Zhang et al, 2011Zhang et al, , 2013aZhang et al, ,b, 2016Hosokawa et al, 2012). Whenever, these structures meet the GNSS signals, they give rise to moderate amplitude and phase scintillation (Hosokawa et al, 2014), especially for polar cap hot patches (Zhang et al, 2017).…”
Section: Fixed Boundary Auroral Emissions (Fbae)mentioning
confidence: 99%